Exploring Lyricstraining in Enhancing Students’ Vocabulary Recognition in English Listening Activities: - Najah Amali Hidayat; Aries Fachriza; Ervin Yudianto (English Teaching Journal : A Journal of English Literature, Language and Education, 2026)
Listening was regarded as an important skill in learning English because it assisted students to communicate with others. Nevertheless, many EFL learners found listening to be problematic due to their lack of vocabulary mastery in dictation activities. The proper learning media were indeed necessary to assist students recognize the vocabulary in listening activity. This study focuses on whether the LyricsTraining application can better strengthen students’ vocabulary recognition in English listening activities compared to YouTube as a learning medium. This was a quantitative study using quasi-experimental non-equivalent control group design. The population was the eighth-grade students of State Islamic Junior High School in East Java in the 2025/2026 academic year. Two classes were taken as the sample, VIII I class as the experimental group with lyrics-training learning and VIII F Class as control group with youtube learning. Quantitative data were collected using pre-tests and post-tests in the form of listening vocabulary recognition tests, followed by analysis with descriptive statistics and the Mann–Whitney U test. The results showed a relevant distinction in between both groups (0.006 < 0.05). It was concluded that LyricsTraining significantly optimize students’ vocabulary recognition in listening activities and could be used as an interactive alternative medium for teaching listening